The Influence of the #MeToo Movement on Socio-Political Dynamics in the MENA Region - Putri, Anggi Koenjaini (JUSS (Jurnal Sosial Soedirman), 2024)
This research explains the influence of the #MeToo movement phenomenon on social and political dynamics in the MENA. Against the backdrop of slow structural change and an authoritarian social contract in the region, the #MeToo movement expanded the space for women and men to overcome cultural taboos regarding gender-based violence. With social movement theory, this research analyses this phenomenon through political opportunities, mobilisation structures, and artistic framing. The analysis results show that the #MeToo movement in MENA gives women and men a voice in fighting gender oppression, changing cultural norms, and demanding policy reform by involving social media as a critical tool to trigger a change in society's perception of sexual violence and provide the impetus for broader reform in women's rights in the region.